Up-regulated Complement 3 Production by Toll-like receptor 9/ Transforming Growth Factor-Beta 1/Complement 3 Pathway in Whole Blood Cells of Lupus Thrombocytopenia - Yi YUAN; Ling ZHAO; Ning MA; Zhuang YE; Zhenyu JIANG; Congqiu CHU (Archives of Rheumatology, 2017)
Objectives: This study aims to assess the complement 3 (C3) expressions in whole blood cells and verify a pathway toll-like receptor 9 (TLR9)/ transforming growth factor-beta 1 (TGF-β1)/C3 for C3 regulation in mediating thrombocytopenia (TCP) in patients with systemic lupus erythematosus (SLE). Patients and methods: The study included 63 newly diagnosed SLE patients (2 males, 61 females; mean age 39.5 years; range 15 to 67 years). Whole blood messenger ribonucleic acid expression for C3, TLR9 and TGF-β1 were measured by quantitative reverse transcription real-time polymerase chain reaction in SLE patients with TCP (n=38) and age- and sex-matched SLE patients without TCP (n=25) at baseline and in 10 SLE patients with TCP after four weeks of treatment. Whole blood cells from SLE patients with TCP were cultured in the presence of TLR9 ligand cytosine-phosphate- guanine, recombinant human TGF-β1, TGF-β receptor inhibitor/activin receptor-like kinase inhibitor SB431542. TGF-β1 and C3 levels in whole blood cells cultures were determined by quantitative reverse transcription real-time polymerase chain reaction and enzyme-linked immunosorbent assay. Results: Whole blood cells from SLE patients with TCP displayed an enhanced gene expression for C3, TLR9 and TGF-β1 compared with that of SLE patients without TCP (p<0.01 for C3, p<0.05 for TLR9 and TGF-β1). SLE patients with TCP had decreased plasma levels of C3 suggesting excessive consumption. In whole blood cell culture, engagement of TLR9 led to the increased gene expression of C3. Furthermore, TGF-β1 inhibitor abolished TLR9 stimulation on C3 gene expression. Conclusion: These results suggest that blood cells are the source of extra-hepatic synthesis of C3 in SLE patients with TCP and this synthesis of C3 was up-regulated by TLR9 via induction of TGF-β1. Thus TLR9/TGF-β1/C3 pathway might be in operation mediating lupus thrombocytopenia.